Extracurricular suggestion web-system using rule-based technique / Syahrom Zamzuri - Zamzuri, Syahrom (2017)
An expert system is a computer application that is seamlessly integrated with display of real world scene and is a growing area in many field studies which solves complicated problems that would otherwise require extensive human expertise. With today technology advancement it is possible to solve problems without seeing an expert within the same room. Choosing the right clubs to join is hard when the new students does not know what are the clubs that available to join, does it suits their preference, what kind of activity the clubs do or what is the benefit that they can get from it. Therefore, this project focused on aiding the new students of UiTM Jasin in choosing suitable extracurricular clubs for them to join by giving options with the help of Student Affair Administration through web-based system. Therefore, this system will fulfil the task. SPIRAL model is used for the development of this web-based system, because the model have the ability which allow developer to improve the system after development for any changes and released it back to the user.